2016
DOI: 10.1071/cp16052
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative nitrogen stress decreases lodging risk and increases yield of irrigated spring wheat in the subtropics

Abstract: In-crop nitrogen (N) application is used widely in rainfed winter wheat production to reduce lodging risk; however, uncertainty exists as to its ability to reduce lodging risk in subtropical irrigated wheat production without simultaneously reducing yield potential. The objective of this study was therefore to determine whether in-crop N application reduces lodging risk without reducing yield of irrigated spring wheat in a subtropical environment. Irrigated small-plot experiments were conducted to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Berry et al [ 7 ] suggested that delay nitrogen fertilizer applications decrease the likelihood of lodging. Similar findings were reported by Peake et al [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Berry et al [ 7 ] suggested that delay nitrogen fertilizer applications decrease the likelihood of lodging. Similar findings were reported by Peake et al [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…So splitting nitrogen fertilization increased lodging and brought no benefit to grain yield. Several studies have reported that lodging reductions have been achieved with sacrificing yield potential by decreasing nitrogen level and delaying nitrogen fertilizer applications [ 7 , 27 – 28 ]. But it remained unclear whether nitrogen management could reduce lodging risk without reducing yield potential.…”
Section: Introductionmentioning
confidence: 99%
“…Plant cell wall components including lignin and cellulose contents enhanced at first and then reduced progressively with the increasing N amounts in wheat [224]. Numerous studies have shown that lodging reduction has been attained at the cost of sacrificing yield potential by reducing N concentration and delaying N fertilizer applications [77,228].…”
Section: Agronomical Managementmentioning
confidence: 99%
“…Beside choosing lodging resistance varieties, husbandry practices also have a significant effect on lodging. Nitrogen management is one of the most common and efficient methods that were used widely in rainfed winter wheat production to reduce lodging risk (Can et al, 2015, Peake et al, 2016and Zhang et al, 2017. Supply the optimum dose of N helps to reduce lodging losses (Telkar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%